Problems with Competence and Leadership Skills of Principals at the Junior High School Level: A Systematic Literature Reviewwords - Agus Pujianto; Sugiarti; Wahyudi Winarjo (Cipta Pustaka Nusantara, 2025)
This study aims to map the development of research and scientific publications on the competencies and leadership skills of school principals at the junior high school (SMP) level. This study uses a Systematic Literature Review (SLR) approach to analyze 103 scientific articles identified through the PRISMA procedure. The articles analyzed were sourced from the Scopus database and published between 2013 and 2024. Data analysis was conducted using bibliometric tools VOSviewer and CiteSpace to identify topic trends, thematic clusters, and scientific contributions in this field. The results of the study revealed four main thematic clusters in the study of principal leadership in junior high schools, namely instructional leadership practices, community involvement and cultural values, knowledge and policy interventions, and assessment and evaluation. The leadership practices cluster was the most dominant theme, reflecting the importance of the principal's role in improving the quality of learning and institutional management. This research contributes to the development of evidence-based and multidisciplinary educational leadership studies and provides a conceptual basis for formulating more contextual and adaptive school principal development policies in response to global challenges. A limitation of this study is the use of data from a single database, Scopus, which does not fully reflect the entire available literature landscape. Therefore, further research is recommended to utilize additional references from reputable databases such as Web of Science and EBSCO.